The diffusion of military power : causes and consequences for international politics - Horowitz, Michael, 1978- (Princeton University Press, 2010)
The Diffusion of Military Power examines how the financial and organizational challenges of adopting new methods of fighting wars can influence the international balance of power. Michael Horowitz argues that a state or actor wishing to adopt a military innovation must possess both the financial resources to buy or build the technology and the internal organizational capacity to accommodate any necessary changes in recruiting, training, or operations. How countries react to new innovations--and to other actors that do or don't adopt them--has profound implications for the global order and the.